Internalisasi Nilai Keteladanan Nabi Muhammad SAW melalui Peringatan Maulid Nabi: Upaya Penguatan Karakter Religius Masyarakat di Bulusidokare, Sidoarjo - Atmari Atmari; Budi Handayani; Sustian Alfina; Dwi Sriwidadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This community service program aims to internalize the exemplary values of the Prophet Muhammad (peace be upon him) through the commemoration of Mawlid al-Nabi as an effort to strengthen the religious character of the community in Bulusidokare, Sidoarjo. The main issue addressed is the tendency for Mawlid activities to remain largely ceremonial, thereby limiting their impact on shaping community attitudes and behavior. The program employed a Participatory Action Research (PAR) approach, involving 45 participants consisting of community members and local leaders. The activities were conducted through stages of collaborative planning, educational sessions, interactive discussions, as well as reflection and evaluation.The results indicate a noticeable improvement in participants’ understanding of the Prophet’s exemplary values, accompanied by positive changes in attitudes and behavior toward more religiously grounded practices. In addition, increased community participation was observed, along with the emergence of individuals acting as local leaders who promote the application of these values within their social environment. These findings suggest that an educational and participatory approach is effective in fostering a deeper and more sustainable internalization of values.In conclusion, the program not only enhances knowledge but also contributes to social transformation through the strengthening of the community’s religious character. This initiative has the potential to serve as a replicable model of community service based on religious values in other contexts.